2018
DOI: 10.1159/000495343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Strength, pH and Chemical Displacers on the Percentage Protein Binding of Protein-Bound Uremic Toxins

Abstract: Background and Objectives: While trying to optimize the dialysis clearances of protein-bound uremic toxins (PBUTs), their percentage protein binding (% PB) is an important parameter. We evaluated the effects of ionic strength, pH change and chemical displacers on the dissociation of PBUTs from albumin in vitro. Methods: PBUTs, such as 3-Carboxy-4-methyl-5-propyl-2-furan-propanoic acid (CMPF), p-cresylsulfate (PCS), indoxyl sulfate (IS) and indole-3-acetic acid (IAA), were spiked with human serum albumin (HSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…To adjust to the main ingredients of ω-6 soybean oil-based lipid emulsion (Intralipid TM ), FAs were prepared by mixing oleic acid and linoleic acid ([linoleic acid]/[oleic acid] = 2) at a final concentration of 1 mmol/L in the inlet blood line of the in vitro HD model based on the established preliminary data [36, 37]. As conformed previously, CMPF, which possesses the highest binding affinity to HSA among the PBUTs tested in the study, was undetectable in the standard bicarbonate dialysate of the control group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To adjust to the main ingredients of ω-6 soybean oil-based lipid emulsion (Intralipid TM ), FAs were prepared by mixing oleic acid and linoleic acid ([linoleic acid]/[oleic acid] = 2) at a final concentration of 1 mmol/L in the inlet blood line of the in vitro HD model based on the established preliminary data [36, 37]. As conformed previously, CMPF, which possesses the highest binding affinity to HSA among the PBUTs tested in the study, was undetectable in the standard bicarbonate dialysate of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we chose CMPF as a representative with high binding affinity at site I of HSA as well as PCS and IS as prototypes tightly binding at site II of HSA. Then, we evaluated the effects of higher ionic strength, pH change, and different Alb displacers on the dissociation of these PBUTs from Alb simultaneously in vitro [36]. Results showed that the inhibitory effects were more remarkable with the addition of binding competitors than that of ionic strength and pH changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al (2019) studied the effects of ionic strength, pH, and chemical displacers on the percentage protein binding (PB) of PBUTs, showing that the PB% decreased with increasing ionic strength, but only a few changes occurred with the increased pH (6.0 to 8.5) [ 67 ]. Regarding chemical displacers, they studied ibuprofen, warfarin, phenylbutazone, indomethacin, furosemide, oleic acid, linoleic acid, and docosahexaenoic acid (DHA), which are known to be typical displacers of HSA sites I or II.…”
Section: Interaction Between Uremic Toxins and Albuminmentioning
confidence: 99%
“…Addition of nanoporous sorbents on the dialysis membrane was shown to increase protein‐bound uraemic toxin removal in a laboratory‐based study (Pavlenko et al, 2017). Reducing protein‐bound uraemic toxin protein binding by increasing blood ionic strength and pH in blood‐purification strategies may be viable options according to in vitro validations (Krieter et al, 2017; Shi et al, 2019). Similarly, competitive binding via chemical displacers is another feasible avenue (Madero et al, 2019; Tao et al, 2016).…”
Section: Special Considerations For Cardiorenal Syndromementioning
confidence: 99%